China and international institutions : alternate paths to global power - Lanteigne, Marc. (London ; New York : Routledge, 2005)
China has shifted its foreign policy from one that avoided engagement in international organizations to one that is now embracing them. These moves present a new challenge to international relations theory. How will the global community be affected by the engagement of this massive global power with international institutions? This new study explores why China has chosen to abandon its previous doctrine of institutional isolation and details how it is currently unable to balance American power unilaterally and details an indirect path to greater power. In addition, it includes.
Chapter INTRODUCTION -- chapter 1 Red light, green light: China and the World Trade Organisation -- chapter 2 Flying geese and rising phoenix: China, APEC and exclusive trade regimes -- chapter 3 Chimeras or peacebuilders? China's new approach to strategic regimes -- chapter 4 Labyrinth's edge: China and the Shanghai Cooperation Organisation -- chapter 5 Seeking modernity: China's institutional openings and shifts in international power.
Includes bibliographical references (pages 202-222) and index.
Print version record.
eBooks on EBSCOhost
Keywords: China -- Foreign relations -- 1976-; China -- Foreign economic relations; International agencies; International Agencies; Chine -- Relations extérieures -- 1976-; Organisations internationales; international organizations; 15.75 history of Asia; 89.90 foreign policy; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; International agencies; International economic relations; Diplomatic relations; China; Foreign policy; International organizations; Economic relations; International cooperation; China; China -- Foreign relations -- 1976-; China -- Foreign economic relations; International agencies; China; Foreign policy; International institutions; International organizations; International economic relations; Kina -- internationella relationer -- 1976-; Kina -- internationell ekonomi; Since 1976; 1950-2000.; 2000-2010.